Job stress among general and special school teachers in Jahrom City, Iran - Alamdarloo, Ghorban Hemati; Moradi, Sajedeh; Moradi, Shahram (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introduction Teaching is among the careers which are associated with a lot of stress. Occupational or job stress is an unfavorable mental state which is caused by the workplace environment and can seriously impede employees’ performance. The purpose of this research was to compare occupational stress among general and special school teachers. Methods 84 teachers (42 were general school teachers and 42 were special school teachers) from Jahrom, Iran were selected as study samples. Special school teachers and general school teachers were chosen using convenience sampling and multistage random sampling methods, respectively. Parker and DeCotiis’s job stress scale was used to assess job stress. The collected data were analysed by two-way analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA). Results Results showed that job stress and its subscales were significantly higher among general school teachers than special school teachers (p <0.05); however, there was no significant difference between male and female teachers in terms of job stress and its subscales (p<0.05). Conclusions According to the findings of this study, the Ministry of Education is recommended to prevent job stress by improving the level of services in general school and holding workshops with the aim of offering teachers some coping strategies to deal with stress in schools.